2000
DOI: 10.1046/j.1365-2702.2000.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Ventilator‐dependent’ children who spend prolonged periods of time in intensive care units when they no longer have a medical need or want to be there

Abstract: • Children who are dependent on ventilators currently spend many months and in some cases years in intensive care units when they no longer have a medical need to be there. • This article presents the views of 18 young ‘ventilator‐dependent’ people (and their parents) who experienced prolonged periods of time in intensive care units and compares their experiences with published literature. • Findings strongly suggest that living in an intensive care unit is inappropriate and detrimental to health and well‐bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
(33 reference statements)
0
20
0
3
Order By: Relevance
“…Milton Hanashiro, 1 Antonio O. C. Franco, 2 Alexandre A. Ferraro, 3 Eduardo J. Troster 4 the ICU by stable patients impairs the capacity to receive new patients with severe conditions, 5 besides the fact that it increases expenditure. 6 As an alternative to lengthy ICU stays, many patients have been transferred to services of lower complexity, such as mechanical ventilator dependency units (MVDUs).…”
Section: Care Alternatives For Pediatric Chronic Mechanical Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Milton Hanashiro, 1 Antonio O. C. Franco, 2 Alexandre A. Ferraro, 3 Eduardo J. Troster 4 the ICU by stable patients impairs the capacity to receive new patients with severe conditions, 5 besides the fact that it increases expenditure. 6 As an alternative to lengthy ICU stays, many patients have been transferred to services of lower complexity, such as mechanical ventilator dependency units (MVDUs).…”
Section: Care Alternatives For Pediatric Chronic Mechanical Ventilationmentioning
confidence: 99%
“…2 This situation exposes patients and their families to problems associated with prolonged hospital stays, such as nosocomial infections, and also psychological 3,4 and relationship disturbances in the family. For the hospital, prolonged bed occupation in…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of children and young people now survive life‐threatening illnesses and traumatic accidents with the aid of sophisticated computerized portable ventilators (Samuels, 1996). Whilst there is evidence that the use of mechanical ventilation can bring about considerable health gain, Noyes (2000) reported concerns that this group of children and young people were frequently remaining in hospital when they no longer had a medical need or wanted to be there.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, Noyes (2000) found that once medically stable, the children and young people did not want to remain in a hospital environment. Living in hospital for prolonged periods of time had a profound and negative impact on the children and their families.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation